2023
DOI: 10.24875/gmm.m21000554
|View full text |Cite
|
Sign up to set email alerts
|

Use of pulmonary ultrasound to predict in-hospital mortality in patients with COVID-19 infection

Abstract: Introduction:Lung ultrasound (LUS) implementation in patients with COVID-19 can help to establish the degree of pulmonary involvement, evaluate treatment response and estimate in-hospital outcome. Objective: To evaluate the application of a LUS protocol in patients with COVID-19 infection to predict in-hospital mortality. Methods: The study was carried out from April 1 to August 1, 2020 in patients with COVID-19 infection admitted to the Intensive Care Unit. Lung evaluation was carried out by physicians traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Full‐text screening yielded 56 articles from which data was subsequently extracted (Figure 1). The characteristics of the included studies are presented in Table [11–63]. Most studies are retrospective, they have a wide distribution worldwide in Italy, Japan, China, Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Full‐text screening yielded 56 articles from which data was subsequently extracted (Figure 1). The characteristics of the included studies are presented in Table [11–63]. Most studies are retrospective, they have a wide distribution worldwide in Italy, Japan, China, Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…A higher LUS score was associated with the need for intensive respiratory support or mechanical ventilation, SpO 2 /FiO 2 ratio below 357 as well as length of stay of ≥9 days ( 21 ). A multiple logistic regression model from a Mexican cohort by Manzur-Sandoval et al found that an LUS score of ≥19 was significantly associated with mortality (hazard ratio =2.55) ( 93 ). Meanwhile, a study by Lugara et al on Southern Italian COVID-19 patients found that increased LUS score correlated with elevated lactate levels and an increased need for ventilation ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la valoración ecográfica pulmonar llevada a cabo en la serie de casos analizados en este estudio, se puede observar que es un excelente indicador de evolución, ya que puntuaciones > 7 fueron consideradas con curso desfavorable y los pacientes requirieron ventilación mecánica invasiva. Esto coincide con lo reportado por Bobillo et al 32 en pacientes pediátricos, así como con otro estudio en población adulta, en el cual las puntuaciones LUS > 6 tuvieron una mala evolución 33 .…”
Section: Discussionunclassified